2008
DOI: 10.1139/f08-030
|View full text |Cite
|
Sign up to set email alerts
|

Growth analysis and age validation of a deepwater Arctic fish, the Greenland halibut (Reinhardtius hippoglossoides)

Abstract: The accuracy of age interpretations on a deep-sea, Arctic fish species, the Greenland halibut ( Reinhardtius hippoglossoides ) was tested using several age validation methods. Consistent annual growth increments were either not formed or not visible in either whole or sectioned otoliths from three fish marked with oxytetracyline and recaptured after 2–4 years at liberty. Bomb radiocarbon assays based on a local reference chronology indicated that both whole and sectioned otoliths underestimated age by 1–15 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 37 publications
2
43
0
Order By: Relevance
“…Nevertheless, halibut live in the same environment as that used to develop the reference chronology for the northwest Atlantic , and thus are well-matched signals. Bomb radiocarbon has also proven effective in validating the accuracy of ageing methods for other flatfish species, including Pacific halibut (Piner and Wischniowski 2004), yellowtail flounder (Limanda ferruginea; Dwyer et al 2003), and Greenland halibut (Treble et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, halibut live in the same environment as that used to develop the reference chronology for the northwest Atlantic , and thus are well-matched signals. Bomb radiocarbon has also proven effective in validating the accuracy of ageing methods for other flatfish species, including Pacific halibut (Piner and Wischniowski 2004), yellowtail flounder (Limanda ferruginea; Dwyer et al 2003), and Greenland halibut (Treble et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The IPHC has greater confidence in age readings of Pacific halibut prepared with break and burn compared to those aged whole (Forsberg 2001); only the former has been validated as producing accurate ages (Piner and Wischniowski 2004). In general, thinsectioning and break-and-burn ageing techniques would be expected to provide more accurate age estimates than surface readings because of the asymmetric growth of old otoliths (Chilton and Beamish 1982;Treble et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For example, tag and recapture data have recently suggested that the growth rate of Greenland halibut may be less than half of what was previously reported (Treble et al, 2008), with current estimates for adult fish ranging from less than 1 cm per year (Albert et al, 2009) to 3 cm per year (Treble et al, 2008). Here we monitored fish over a complete year and therefore were able to provide the first data on growth in captivity.…”
Section: Discussionmentioning
confidence: 87%
“…13) is oxytetracycline (OTC) marking of juveniles in order to follow growth increments in the otoliths from the time of marker injection (e.g. Greenland halibut: Treble et al 2008). …”
Section: Longevitymentioning
confidence: 99%